Human + AI for Enhanced Security: Creating Resilient Systems through Collaboration - Sudheer Kotilingala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapidly evolving threat landscape demands a paradigm shift in cybersecurity approaches, moving beyond traditional siloed defenses. This article explores how the integration of human expertise with artificial intelligence creates robust security frameworks capable of addressing sophisticated modern attacks. The complementary nature of these components—with AI excelling at processing speed, pattern recognition, and continuous monitoring, while human analysts provide contextual understanding, ethical judgment, and adaptive reasoning—forms the foundation for resilient security operations. Through practical applications in real-time threat detection, automated incident response, enhanced decision-making, and false positive reduction, organizations can implement comprehensive defense mechanisms that evolve alongside increasingly sophisticated adversaries. Key implementation considerations span both technical requirements and human factors, emphasizing that effective security stems not from choosing between human or artificial intelligence but from thoughtfully integrating both to maximize their complementary strengths.